A bifunctional hierarchical porous kaolinite geopolymer with good performance in thermal and sound insulation. (10th August 2020) - Gao, Huan; Liu, Hao; Liao, Libing; Mei, Lefu; Zhang, Fan; Zhang, Longhui; Li, Sha; Lv, Guocheng
Highlights: A bifunctional hierarchical porous geopolymer with kaolinite was prepared. Great thermal insulation and sound insulation performances. The density is 0.086 g·cm −3 and compressive strength is high (0.27 MPa). The pore diameter can be adjusted from 0.20 to 2.48 mm. Abstract: Thermal and sound insulation materials are crucial for reducing the energy consumption and noise pollution of building, but these two types of materials are generally developed independently. Here, a new type of bifunctional hierarchical porous geopolymer which can effectively reduce heat transfer and noise sound is proposed and it is synthesized with inexpensive kaolinite as main raw material through an energy-saving method. The optimal porous geopolymer products show high porosity (93.80%) and extremely low density (0.086 g·cm −3 ) but relatively high compressive strength (0.27 MPa). More importantly, they have low thermal conductivity (0.040 W·m −1 ·K −1 ) but high sound absorption coefficient (0.539 at 5000 Hz; 0.809 at 500 Hz with gap of 50 mm) and sound reduction index (38.6 dB at 2000 Hz). Therefore, this hierarchical porous geopolymer can be potentially used as a new type of bifunctional building material to reduce the energy consumption and noise pollution of building at the same time.